'For You One Flesh': Allusions to Genesis 2:4-3:24 and the Construction of Male-Female Relationships in Select Second Temple Texts - Brown, Katie (School of Religion, Theology, and Peace Studies, 2023)
Throughout history, countless writers have ventured to explore the myriad of questions that arise from the short but deeply enigmatic text of Genesis 1-3. In particular, the Eden narrative of Genesis 2:4b-3:24 has been cited as a major influence over Judeo-Christian understandings of gender and sexuality. Due to its prominent place in western culture, ideas relating the first woman to the origin of sin and the fallen state of mankind are engrained in our psyche, negatively influencing relations between the sexes. However, many of the common assumptions that prevail regarding this text are not to be found in the original Hebrew text itself, and instead, are a culmination of centuries of disparate interpretations arising from particular social, political, and cultural contexts. This thesis is concerned with examining how male-female relations, in particular marital relations, were explained and justified through allusions to Genesis 2-3 in its earliest interpretations, in the late Second Temple period. Four texts will be examined in greater detail; Sirach, Tobit, 4QInstruction, and Ephesians, so as to limit our investigation purely to allusions and references, rather than explicit exegesis or rewritings of the Eden narrative.
Keywords: Biblical Interpretation, Second Temple Judaism, Gender and Sexuality Studies